2023
DOI: 10.1186/s12967-023-04510-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs/DNMT3B axis in human cancers: from pathogenesis to clinical significance

Chunjie Huang,
Paniz Azizi,
Masoud Vazirzadeh
et al.

Abstract: Cancer is a complex disease with many contributing factors, and researchers have gained extensive knowledge that has helped them understand the diverse and varied nature of cancer. The altered patterns of DNA methylation found in numerous types of cancer imply that they may play a part in the disease’s progression. The human cancer condition involves dysregulation of the DNA methyltransferase 3 beta (DNMT3B) gene, a prominent de novo DNA methyltransferase, and its abnormal behavior serves as an indicator for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 101 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…This observation leads to speculation that the notable distinctions in organism complexity between higher and lower organisms could potentially stem from the substantial variations in noncoding transcripts. Many of these noncoding transcripts undergo intricate processing, resulting in the generation of smaller noncoding RNA entities, such as miRNA and lncRNA [ 41 ]. By engaging with proteins, RNA, and DNA noncoding RNAs have arisen as pivotal modulators of gene expression in both pathological and physiological conditions.…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
“…This observation leads to speculation that the notable distinctions in organism complexity between higher and lower organisms could potentially stem from the substantial variations in noncoding transcripts. Many of these noncoding transcripts undergo intricate processing, resulting in the generation of smaller noncoding RNA entities, such as miRNA and lncRNA [ 41 ]. By engaging with proteins, RNA, and DNA noncoding RNAs have arisen as pivotal modulators of gene expression in both pathological and physiological conditions.…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
“…The advent of targeted therapies has markedly prolonged the survival of patients with mutations in key driver genes such as EGFR, ALK, MET, ROS1, RET, and HER2 [ 3 ]. Nevertheless, a significant fraction of LUAD patients do not possess these mutations, highlighting the critical need for identifying new actionable driver genes [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrastingly, Minderman's study revealed expression of PD-L1 or 9p24.1/PD-L1/2 CNA was detected in only a small number of samples. In addition, their team extracted PD-L1 messenger RNA (mRNA) expression data from publicly available databases for validation, and they found that there was no enhancement of PD-L1 expression in PTL compared to primary mediastinal B-cell lymphomas (PMBCLs) [ 16 19 ]. Instead, HLA deletions were common in their PTL cohort.…”
Section: Introductionmentioning
confidence: 99%